Enterprise and organizational modeling and simulation : 15th International Workshop, EOMAS 2019, held at CAiSE 2019, Rome, Italy, June 3-4, 2019, Selected Papers /: 15th International Workshop, EOMAS 2019, held at CAiSE 2019, Rome, Italy, June 3-4, 2019, Selected Papers. (2019) - Unknown
No abstract available